Successful Implementation of the Exercise First Approach for Intermittent Claudication in the Netherlands is Associated with Few Lower Limb Revascularisations. (December 2020) - Jansen, Sandra C.P.; van Nistelrooij, Lambertus P.J.; Scheltinga, Marc R.M.; Rouwet, Ellen V.; Teijink, Joep A.W.; Vahl, Anco C.
Abstract : Objective: A stepped care model, in which patients are primarily treated with supervised exercise therapy (SET), is recommended as the optimal strategy for intermittent claudication (IC). The aim of this study was to determine the primary treatment (SET, endovascular revascularisation [ER], or open surgery) in relation to secondary lower limb revascularisation and survival in patients with IC. Methods: This study was a nationwide retrospective data analysis of health insurance claims of patients newly diagnosed with IC between January 2013 and December 2017. Exclusion criteria were the presence of diagnostic codes for critical limb ischaemia or for a diabetic foot. Study outcomes were distribution of primary treatment modalities, freedom from secondary lower limb revascularisation, and overall five year survival. Analysis included Kaplan–Meier method and Cox proportional hazards regression models with adjustment for multiple confounders (age, gender, socioeconomic status, use of diabetes medication, statins, platelet aggregation inhibitors or anticoagulants, presence of cardiac disease, chronic obstructive pulmonary disease, and pre-dialysis). Results: The five year cohort included 54 504 patients with IC (primary SET n  = 39 476, primary ER n  = 11 769, and primary open surgery n  = 3 259). SET as primary treatment increased from 63% in 2013 to 87% in 2017. Patients who underwent ER or open surgery as a primary treatment had a higher risk of secondary revascularisations (hazard ratio [HR] 1.44; 95% confidence interval [CI] 1.37–1.51; p  < .001 and HR 1.45; 95% CI 1.34–1.57; p  < .001, respectively) and a higher mortality risk compared with SET as a primary treatment (HR 1.38; 95% CI 1.29–1.48; p  < .001 and HR 1.49; 95% CI 1.34–1.65; p  < .001, respectively). Conclusion: Guideline adherence improved to 87% in Dutch patients with IC. Patients receiving primary SET had fewer lower limb revascularisations and demonstrated better survival than patients undergoing primary ER or open surgery.